2006
DOI: 10.1097/01.crd.0000182411.88146.72
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Disease in South Asians

Abstract: Coronary artery disease (CAD) is a leading cause of morbidity and mortality worldwide and was responsible for 7.2 million deaths in 2003. Various studies have pointed out that South Asians have a higher prevalence of CAD as compared with other ethnicities. South Asians may have a genetic predisposition to CAD; however, environmental, nutritional, and lifestyle factors may also be responsible. South Asians have a much higher prevalence of metabolic syndrome, diabetes, insulin resistance (and resultant hyperinsu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 59 publications
5
31
1
Order By: Relevance
“…The prevalence of diabetes, hypertension and low HDL in this population is consistent with previously reported data [3,43,44]. However, the literature has shown that traditional risk factors for CAD may not fully explain the excessive CAD risk in South Asians as compared to Caucasians, and the search for other markers is required, especially for this population [6,45].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The prevalence of diabetes, hypertension and low HDL in this population is consistent with previously reported data [3,43,44]. However, the literature has shown that traditional risk factors for CAD may not fully explain the excessive CAD risk in South Asians as compared to Caucasians, and the search for other markers is required, especially for this population [6,45].…”
Section: Discussionsupporting
confidence: 89%
“…We could not find an association of other CAD risk factors with pro-inflammatory HDL, and there is no plausible explanation except the small sample size. Similarly, several studies have shown Lpa to be a risk factor for CAD as well as carotid IMT [43,44]. We could not find this association in our study, however Lpa was associated with dysfunctional HDL measured by HDL inflammatory Index (Table 4).…”
Section: Discussioncontrasting
confidence: 51%
“…Migrant populations carry along disease characteristics, inherited from their place of origin, 11 which affect future risk of CVD. The CVD risk profile among migrant populations, however, may change over time as they get exposed to the factors of their host environment.…”
Section: Boateng Et Al Cardiovascular Disease Risk Among Ghanaian Migmentioning
confidence: 99%
“…South Asian knowledge of and attitudes to health risks a uK National Health service survey found that many sas are unaware of their increased risk of CVD and T2D. Even when they have developed disease, sas are often not aware of related causes and complications or preventive measures, such as healthier foods or cooking methods, despite public health campaigns and publicity 14,50,51 . an additional problem is that sas are reluctant to accept that amelioration of their condition is within their control.…”
Section: South Asians and Key Cvd Risk Factorsmentioning
confidence: 99%